2012
DOI: 10.1186/1756-0500-5-663
|View full text |Cite
|
Sign up to set email alerts
|

Survival of patients with alcoholic and cryptogenic cirrhosis without liver transplantation: a single center retrospective study

Abstract: BackgroundThere is no recent data addressing the long term survival of cirrhosis patients without transplantation, but with the availability of optimal pharmacological and endoscopic therapies. We compared the long term transplant free survival of alcoholic (AC) and cryptogenic (CC) cirrhosis patients in a setting where liver transplantation was, until very recently, not available. AC and CC patient details were extracted from our database, maintained since 1995. For those who had not attended clinics within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 28 publications
3
28
0
Order By: Relevance
“…In Sri Lanka, Senanayake et al . demonstrated that cryptogenic cirrhosis patients had a similar survival rate to cases with alcoholic cirrhosis . The main cause of mortality in both cryptogenic and alcohol‐related cirrhosis was liver‐related in this cohort of Sri Lankan patients.…”
Section: Discussionsupporting
confidence: 51%
“…In Sri Lanka, Senanayake et al . demonstrated that cryptogenic cirrhosis patients had a similar survival rate to cases with alcoholic cirrhosis . The main cause of mortality in both cryptogenic and alcohol‐related cirrhosis was liver‐related in this cohort of Sri Lankan patients.…”
Section: Discussionsupporting
confidence: 51%
“…Hepatitis B and hepatitis C prevalence is very low even among presumed “high risk” populations . Chronic viral hepatitis related CLD is also rare (<2% for HBV and <1% for HCV related cirrhosis) . Instead, alcoholic and cryptogenic or NASH‐related forms of cirrhosis predominate .…”
Section: Introductionmentioning
confidence: 99%
“…Chronic viral hepatitis related CLD is also rare (<2% for HBV and <1% for HCV related cirrhosis) . Instead, alcoholic and cryptogenic or NASH‐related forms of cirrhosis predominate . We previously reported that 63% of cases referred for liver transplantation were related to NASH‐cirrhosis .…”
Section: Introductionmentioning
confidence: 99%
“…This has led to an increasing contribution of nonalcoholic steatohepatitis to the burden of cirrhosis [4]. This has led to an increasing contribution of nonalcoholic steatohepatitis to the burden of cirrhosis [4].…”
Section: Introductionmentioning
confidence: 99%
“…Liver transplantation is in its infancy and it is still not widely available for most cirrhotic patients attending state sector hospitals [4]. Liver transplantation is in its infancy and it is still not widely available for most cirrhotic patients attending state sector hospitals [4].…”
Section: Introductionmentioning
confidence: 99%